Upaya Meningkatkan Keaktifan Peserta Didik pada Pembelajaran Fikih melalui Model Market Place Activity di MAN 3 Kulon Progo - Munji Jakfar (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2018)
This study is a follow-up to the teacher to solve the problems in learning Jurisprudence XI IPA 2 MAN 3 Kulon Progo. After an evaluation by mendam associated with low absorptive capacity of students to the subject matter of jurisprudence conclusion: a) Low participation of learners in the learning, b) Low learning outcomes of students. Based on these problems, this study aims to enhance the activity of students in learning by using Learning Model Jurisprudence Market Place Activity. This study was conducted in two cycles. Each cycle consists of four activities: planning, action, observation and reflection. The research subject of students grade XI 2 MAN 3 Kulon Progo. Data collected through documentation, observation, interviews, field notes and research instruments. Analysis of the data was done by reducing the data, presenting data, and draw conclusions. The results showed, (1) an increase in active learners in the following study of jurisprudence before action learning activities of students on average by 46.75% or 12 learners, after the action on the first cycle increased 81.73% or 21 participants students, then on the second cycle increased by 93% or 24 learners., (2) an increase in the study of students, before action is taken the number of students who pass 19% or 5 learners. Then, after the action on the first cycle, the number of students who completed 69.2% or 18 learners. After the implementation of the action on the second cycle the number of students who completed 100% or complete all.